OBSERVATION OF SIMULATED ACID RAIN IMPACT ON CHICKPEA PLANT - Khan, Abrar Ahmad; Khan, Mustabeen (Ecoprint: An International Journal of Ecology, 2014)
The effect of simulated acid rain (SAR) on plant growth, yield and photosynthetic pigments ofchickpea (Cicer areitinum L.) var.T-3 was studied in glass house condition. Three acidity levels, pH5.0, 4.0 and 3.0 (IN H2S04 and IN HN03) were applied twice in a week on chickpea plants. Symptomslike yellowing, lesions on lamina and marginal necrosis were observed with variations in alltreatments. Plant growth, yield and photosynthetic pigments were reduced in all the treatments beinghighest at pH 3.0. Thus acid rain was found harmful to chickpea crop. DOI: http://dx.doi.org/10.3126/eco.v20i0.11468 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 77-80